2017
DOI: 10.1177/0284185116685925
|View full text |Cite
|
Sign up to set email alerts
|

MRI diagnosis of carpal boss and comparison with radiography

Abstract: Background: A carpal boss is a potentially painful bony mass in the region of the second or

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…This is increased compared with the 28% (16 out of 57) reported in the Mespreuve group in 2017 [9]. This likely reflects subject selection criteria, as all of our subjects reported dorsal wrist pain and previous trauma or history of wrist overuse.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This is increased compared with the 28% (16 out of 57) reported in the Mespreuve group in 2017 [9]. This likely reflects subject selection criteria, as all of our subjects reported dorsal wrist pain and previous trauma or history of wrist overuse.…”
Section: Discussionmentioning
confidence: 53%
“…Although the painful carpal boss is a well-published clinical syndrome, little work has examined the relationship between biomechanical avulsive forces at the ECRB insertion and symptoms/anatomical variations. Mespreuve et al reviewed 57 subjects with carpal boss who underwent radiography and MRI, and reported that 73% of the patients had fused carpal bosses, 4% had partial coalitions, and the remaining 23% had an os styloideum [9]. Goiney et al reviewed 129 wrist CTs of the general population with no suspicion of dorsal wrist pain or carpal boss, and reported a very high proportion of subjects (82%) showing a dorsal protuberance, 7% showing an os styloideum, and 11% showing no carpal boss [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Quadrangular joint traumata may result in bony carpal boss [19]. Although the restricted motion, deformations induce juxtaarticular changes (Figure 10A–C).…”
Section: Pathology and Imagingmentioning
confidence: 99%